2018
DOI: 10.1037/rel0000134
|View full text |Cite
|
Sign up to set email alerts
|

Faith concepts in psychology: Three 30-year definitional content analyses.

Abstract: How does the psychology of religion literature define the terms religiousness, spirituality, faith, and sacred? Despite the growing interest in and recognition of spirituality and religiousness in psychology, these faith constructs remain poorly defined. We conducted a literature review, comparing existing definitions of these 4 constructs, looking for a consensus, and presenting 4 preliminary working definitions based on the literature. We then undertook 3 studies to find out the prototype phenomena being use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 97 publications
(181 reference statements)
2
62
0
Order By: Relevance
“…Research supports Frankl's definition of meaning in terms of a search for self-transcendence. For example, Harris et al (2018) showed that finding meaning is an essential element of self-transcendence. McClintock (2015) reported that selftranscending gratitude may be the very key to how we can become change agents of making a difference in the world.…”
Section: Frankl's Self-transcendence Modelmentioning
confidence: 99%
“…Research supports Frankl's definition of meaning in terms of a search for self-transcendence. For example, Harris et al (2018) showed that finding meaning is an essential element of self-transcendence. McClintock (2015) reported that selftranscending gratitude may be the very key to how we can become change agents of making a difference in the world.…”
Section: Frankl's Self-transcendence Modelmentioning
confidence: 99%
“…Religiousness denotes beliefs, practices and experiences linked with organized traditions (Cheadle & Dunkel Schetter, 2017) which also include spirituality (Harris et al, 2018). Hindu religion is one of the oldest religions and its present form has been evolved from a long assimilation process.…”
Section: Introductionmentioning
confidence: 99%
“…Defining terms and setting parameters for a discipline or particular scope of scholarship is not unique to Islamic psychology. Scholars in the domain of psychology of religion and spirituality have long struggled to define the terms 'religion' and 'spirituality' , how these terms overlap, how they are different, and of course it is debated how one can study something that is not even properly defined (see Harris, Howell, & Spurgeon, 2018). In such cases, scholars end up having to rely on operationalized definitions of terms as opposed to generally agreed upon ones, with both scenarios having pros and cons.…”
Section: Discussionmentioning
confidence: 99%